Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Collective Identity Profiles: The Case of Francophones in Manitoba - Levesque, Annabel; Gueye, N’deye Rokhaya; Rivard, Étienne; de Moissac, Danielle; Archambault, Hélène (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Abstract This quantitative study seeks to explore collective identity profiles that emerge among French-speaking adolescents and young adults in Manitoba. A total of 493 participants completed a questionnaire measuring their level of identification with Francophone and Anglophone identities, their perception of continuity with respect to the future of the French language and culture in Manitoba, and their mental wellbeing. The results of a cluster analysis revealed four collective identity profiles, namely Bilingual Optimist, Franco-Dominant Optimist, Indifferent Pessimist, and Anglo-Dominant Pessimist. Participants who belonged to each of these profiles differed in terms of their age, their mother tongue, the type of school they attended, and their gender. Moreover, collective identity profiles were linked to participants’ mental wellbeing, with those in the Bilingual Optimist profile and those in the Franco-Dominant Optimist profile demonstrating a significantly higher level of mental wellbeing compared to the other two profiles. Keywords: collective identity profiles, mental wellbeing, Francophone minorities, adolescence, young adulthood Résumé Cette étude quantitative visait à explorer les profils identitaires collectifs qui émergent naturellement chez les adolescents et les jeunes adultes francophones du Manitoba. Un total de 493 participants ont rempli un questionnaire mesurant leur niveau d'identification aux identités francophone et Anglophone, leur perception de continuité quant à l'avenir de la langue et de la culture françaises au Manitoba, et leur bien-être mental. Les résultats d'une analyse de classification ont révélé quatre profils identitaires collectifs émergeant, soit Bilingue optimiste, Franco-dominant optimiste, Indifférent pessimiste et Anglo-dominant pessimiste. Les participants appartenant à chacun de ces profils se distinguent par leur âge, leur langue maternelle, le type d'école qu'ils fréquentent et leur genre. De plus, les profils identitaires collectifs étaient liés au bien-être mental des participants, avec ceux du profil Bilingue optimiste et ceux du profil Franco-dominant optimiste ayant un niveau de bien-être mental significativement plus élevé par rapport aux deux autres profils. Mots-clés : profils identitaires collectifs, bien-être mental, minorités francophones, adolescents et jeunes adultes

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.